Docetaxel-associated palmar-plantar erythrodysesthesia: A case report and review of the literature. (February 2014) - Harris, Christy S; Wang, Dorothy; Carulli, Alison
Docetaxel-associated palmar-plantar erythrodysesthesia is rarely reported in literature, particularly when used in the treatment of sarcomas. Here, we report a case of docetaxel-related palmar-plantar erythrodysesthesia in a 28-year-old male with recurrent Ewing sarcoma. Although palmar-plantar erythrodysesthesia has been seen in the literature for 30 years, there has still been little progress in understanding and appropriately addressing this adverse effect. This case report and literature review illustrates an infrequently documented adverse skin reaction and discusses the etiology, presentation, and available treatment options for palmar-plantar erythrodysesthesia.